Pengaruh Financial Technology dalam Membantu Perkembangan UMKM di Indonesia - Utami, Daffa Mega; Sutisna, Reihan Muhammad; Simbolon, Sriagnes; Hamdal, Nanda Hashabul (Universitas Pahlawan Tuanku Tambusai, 2024)
In this study there is a focus on how Financial Technology has influenced the growth of small and medium enterprises (MSMEs). FinTech, short for